Предмет: Алгебра,
автор: 121312xy
x^3+8x^2-4x-32=0
x^2(x-3)+9(3-x)=0
Решите уровнения
Ответы
Автор ответа:
0
Ответ:
Объяснение:
x^3+8x^2-4x-32=0
х² (х + 8) -4(х+8) = 0
(х+8) * (х² - 4) = 0
(х+8)*(х+2)*(х-2) = 0
Первый корень:
х+8 = 0
х = -8
Второй корень:
х+2=0
х = -2
Третий корень:
х-2 = 0
х = 2
Ответ: -8; -2; 2
x^2(x-3)+9(3-x)=0
х²(х-3) -9(х-3) = 0
(х-3)*(х²-9) = 0
(х-3)*(х-3)*(х+3) = 0
(х-3)²*(х+3) = 0
Первый корень:
х-3 = 0
х =3
Второй корень:
х+3 = 0
х = -3
Ответ: -3; 3
Похожие вопросы
Предмет: Русский язык,
автор: fooxx
Предмет: Геометрия,
автор: Squirrel14
Предмет: Русский язык,
автор: simona23
Предмет: Математика,
автор: dariadrozdova2
Предмет: Алгебра,
автор: bibigulomarova1